Numerical Analysis of Seepage Failure Modes of Sandy Soils within a Cylindrical Cofferdam - Aissa Bensmaine; Naima Benmebarek; Sadok Bensmebarek (Civil Engineering Journal, 2022)
Soil seepage failure within cofferdams is a dangerous phenomenon that always poses difficulties for designers and builders of excavations in zones with high water levels. When the hydraulic head difference H between the upstream and downstream sides reaches a critical height, the downstream soil seepage failure occurs. Depending on soil properties, soil-wall interface characteristics, and cofferdam design, different seepage failure modes can be observed: heaving, boiling, liquefaction, or failure by reduction of the passive earth pressure. In the literature, there are differences, sometimes very large, in the critical value of the hydraulic head loss Hc/D inducing seepage failure given by several methods proposed for stability verification. Then, complex cases are generally approached using simplifying assumptions and adopting large safety factors to take account of uncertainties. In practice, geotechnical engineers deal with many kinds of excavations and different shapes of cofferdams, such as rectangular, square, or circular, which generate three-dimensional (3D) flow conditions. Axisymmetric seepage flow through the soil in a circular cofferdam is often used to model such 3D seepage flow. In this paper, using the numerical code FLAC, several numerical simulations are carried out in axisymmetric groundwater flow conditions to analyze the seepage failure modes of cohesionless sandy soils within a cylindrical cofferdam. The effects of the cofferdam radius, internal soil friction, soil dilatancy, and interface friction on the Hc/D value and failure mode are studied. The numerically obtained seepage failure modes are presented and discussed in various scenarios. The present results, illustrated in both tables and graphs, show a significant decrease in the value of Hc/Dinducing seepage failure, with a decrease in the cofferdam radius. They also indicate the sensitivity of the seepage failure mode to internal soil friction, soil dilatancy, interface friction, and cofferdam radius. As well, new terms are proposed for the seepage failure mode designations based on the 3D view of the downstream soil deformation. Doi: 10.28991/CEJ-2022-08-07-06 Full Text: PDF